PENERAPAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DALAM MENGIDENTIFIKASI MASALAH KERUSAKAN PRODUK PAKAN AYAM PADA PT. JAPFA COMFEED INDONESIA, TBK UNIT LAMPUNG - Marcelly Widya Wardana; Sulastri Sulastri; Siti Hasanah (Universitas Ahmad Dahlan Indonesia, 2019)
PT. Japfa Comfeed Indonesia, Tbk Unit Lampung is a company engaged in the field of animal feed with two types of products, namely pellet and crumble. The real condition that often occurs in this company is that there is a final product that has problems in animal feed that is not in accordance with predetermined quality standards. The purpose of this study is to analyze failures that cause product defects by using the Failure Mode and Effect Analysis (FMEA) method, getting the risk of the biggest production process failure in the RPN (Risk Priority Number) value, and proposing improvements for subsequent production. The method used in this study uses statistical tools in the form of check sheets, p control maps and Cause Failure Mode Effect (CMFE) analysis. The results of the control chart analysis show that chicken feed is within the control limit, and the highest Risk Priority Number (RPN) value is the filter with a value of 100 RPN so that the pellet can pass the final stage. To overcome this problem, the proposed improvement is to add a filter to the crumble machine and then carry out routine maintenance and inspection.